ESTUDOS DO PROCESSO DE QUEIMA DA CERÂMICA PRÉ-HISTORICA DO SÍTIO ARQUEOLÓGICO SERRA DO EVARISTO I - BATURITÉ-CE/BRASIL. - Claudia Oliveira; Lucila E. P. Borges; Igor Pedroza; Emília A. Arnaldo; Viviane Castro; Neuvânia C. Ghetti (Universidade do Oeste Paulista, 2016)
This investigation evaluated the burn process in prehistoric ceramic from the Serra do Evaristo I, an archaeological site, located in Baturité, Ceará, in Northeast Brazil. The material analysis shows variation in the material coloration that can indicate different burning processes. However, in a prehistoric and ethno-historic context of the groups from the Brazilian northeast, the usual data shows only the burning process in an oxidant atmosphere. Therefore, there remains a question concerning whether this variation is related to different production processes of the ceramic material or to the different types of the clays. With the objective of clarifying this question, X-Ray Diffractometry (RXD) petrographic analysis were performed on the material. It was verified and shown that the Serra do Evaristo I ceramists used two types of clays originating from two different places and that they could mix the two clay minerals according to the type of vessels that were produced.